Impact of electrochemotherapy in metastatic cutaneous melanoma: a contemporary systematic review and meta-analysis. (4th May 2022) - Petrelli, Fausto; Ghidini, Antonio; Simioni, Andrea; Campana, Luca Giovanni
Abstract: Background: Electrochemotherapy (ECT) harnesses electric pulses to enhance cytotoxic drug delivery into tumors and has entered the armamentarium to treat superficially metastatic melanoma. We performed a systematic review and meta-analysis to assess treatment patterns and patient outcomes. Methods: PubMed, Medline, Embase, and the Cochrane Library databases were queried for publication from inception to September 2020. Primary outcome measures were overall and complete response rate (ORR and CRR); secondary outcomes included local control rate (LCR) and overall survival (OS). Results: Twenty-seven studies met the selection criteria for a total of 1161 individuals (mean age 71 years) and 5308 tumors (weighted mean size 14 mm). The majority of patients ( n  = 1124) underwent bleomycin-ECT. Aggregate ORR was 77.6% (95% confidence interval [CI] 71.0 − 83.2%) and CRR 48% (95% CI 42 − 54%), with no significant difference between the route of bleomycin administration (ORR, 69.2 vs. 81.9% following intravenous or intratumoral bleomycin, p =  .37) and tumor size ( p =  .69). When reported ( n  = 8 studies), 1- and 2-year LCR ranged from 54 to 89% and 72 to 74%, respectively, and 1-year OS ( n  = 3 studies) from 67 to 89%. Conclusions: ECT with either intratumoral or intravenous bleomycin confers a high therapeutic response in cutaneous metastatic melanoma. Moderate evidence supports its low toxicity and durability of local control. Highlights: Electrochemotherapy (ECT) is associated with a 77% overall response rate (ORR). Intravenous and intratumoral bleomycin are equally effective. There are no relevant toxicity concerns. One-year local tumor control rate ranges from 54 to 89%. Current literature has significant variation in reporting.